Multifaceted Regulations of the Serotonin Transporter: Impact on Antidepressant Response - Baudry, Anne; Pietri, Mathea; Launay, Jean-Marie; Kellermann, Odile; Schneider, Benoit (Frontiers in Neuroscience, 2019)
Serotonin transporter, SERT (SLC64A for solute carrier family 6, member A4), is a twelve transmembrane domain protein that assumes the uptake of serotonin (5-HT) through dissipation of the Na+ gradient established by the electrogenic pump Na/K ATPase. Abnormalities in 5-HT level and signaling have been associated with various disorders of the central nervous system such as depression, obsessive-compulsive disorder, anxiety disorders, and autism spectrum disorder. Since the 50’s, SERT has raised a lot of interest as being the target of a class of antidepressants, the Serotonin Selective Reuptake Inhibitors (SSRIs), used in clinics to combat depressive states. Because of the refractoriness of two-third of patients to SSRI treatment, a better understanding of the mechanisms regulating SERT functions is of priority. Here, we review how genetic and epigenetic regulations, post-translational modifications of SERT, and specific interactions between SERT and a set of diverse partners influence SERT expression, trafficking to and away from the plasma membrane and activity, in connection with the neuronal adaptive cell response to SSRI antidepressants.